When Readers Ask Questions: Inquiry‐Based Reading Instruction. (24th May 2016) - Ness, Molly
Abstract: When literacy instruction is driven by student‐generated questions, students are able to dive deeper into text. This article explores the cognitive and motivational benefits of question generation to foster reading comprehension. The author presents classroom vignettes where students become inquisitive readers by posing their own questions. As they generate questions within and beyond the text, these authentic student inquiries promote reading comprehension and text engagement.